Ab initio modelling of calcium phosphate clusters and their vibrational spectra - Boldeskul, I.E.; Sukhodub, L.F.; Kalinkevich, A.N.; Khavryutchenko, V.D. (Condensed Matter Physics, 2006)
Calcium phosphate and hydroxylcalcium phosphate clusters that model amorphous phase elementary unit cells as well as their vibrational spectra were calculated by ab initio quantum chemical method using GAMESS code. Normal coordinate analysis was accomplished for phosphate anion, tricalcium phosphate and hydroxylapatite. Calculated IR-spectra and spectra of inelastic neutron scattering were defined in comparison with experimental data. It was shown that within the suggested approach, vibrational spectroscopy appears to be a reliable method of verifying the quantum chemical calculated structure versus the experimental data.